Korean Red Ginseng: benefits versus precautions - Makky, Essam A. (Bio-Byword Scientific Publishing, 2018)
Over the years, Korean red ginseng (RG), scientifically known as Panax ginseng, has been used to treat several diseases. It is a prominent and ancient medicinal herb in the Orient. Ginseng ginsenoside is the major component of RG which has been presumed to be responsible for the health benefits of RG. Many studies on P. ginseng have until now concentrated on the mechanism of action of the individual components of RG. However, despite the numerous research on the molecular basis of P. ginseng activities, it is still confusing how several active components can simultaneously interact with several targets to give the diverse effects in different diseases. This overview covered the positive and negative effects of using the Korean RG; it also outlined the major chemical components of the Korean RG.